Association Between D-dimer and Early Adverse Events in Patients With Acute Type A Aortic Dissection Undergoing Arch Replacement and the Frozen Elephant Trunk Implantation: A Retrospective Cohort Study - Liu, Tong; Zheng, Jun; Zhang, You-Cong; Zhu, Kai; Gao, Hui-Qiang; Zhang, Kai; Jin, Xiu-Feng; Xu, Shang-Dong (Frontiers in Physiology, 2020)
Objective In the present study, we investigated the associations between D-dimer levels at admission and early adverse events in patients with acute type A aortic dissection undergoing arch replacement and the frozen elephant trunk (FET). Methods We retrospectively analyzed data of patients with acute type A aortic dissection undergoing aortic arch surgery and FET from July 2017 to December 2018 at Beijing Anzhen Hospital. D-dimer levels were evaluated within 24 h of admission. Multivariate Cox regression analysis was used to determine independent predictors of early postoperative adverse events. Results A total of 347 patients were included in the study. The average age of the patients was 48.07 ± 10.56 years, with male predominance (79.25%). The incidence of 90-day postoperative adverse events was 18.7%, consisting of 14.7% mortality and 4.0% permanent neurological dysfunction (PND). The median D-dimer level was 1.95 ug/ml (interquartile range, 0.77–3.16 ug/ml). Multivariable Cox regression analysis revealed that D-dimer level was independently associated with 90-day postoperative adverse events after adjustment for confounding factors (hazard ratio = 1.19 per 10 ug/ml increase in D-dimer, 95% confidence interval: 1.01–1.41; P = 0.039). Kaplan–Meier analysis revealed that the highest tertile (median 6.27 ug/ml) had more 90-day postoperative adverse events compared with the median and lowest tertiles (P = 0.0014). Sub-analysis found that the association remained unchanged. Conclusion Increased D-dimer levels at admission were associated with 90-day postoperative adverse events in patients with acute type A aortic dissection undergoing arch replacement and FET. These results may help clinicians optimize the risk evaluation and perioperative clinical management to reduce early adverse events. Key Question Explore the relationship between D-dimer and early outcomes in patients with aortic dissection with arch replacement. Key Findings Increased D-dimer at admission was associated with adverse events in patients with aortic dissection with arch surgery. Take-Home Message The high-risk patients deserve close medical monitoring.